8th European Championship for women. FYRO Macedonia 2008. Qualitative trend analysis - Pollany, W. (EHF, 2009)
1. More and more elements of male handball are transferred to the women game. - Team moves disappear one by one, the dominant tactical elements are group tactics 2-2 or 3-3. - Shots are fired as fast jump shots or forearm shots over the LP. - The turnover play has improved tremendously, therefore the fastbreak concepts are based on single or group fastbreak, team concepts have vanished. - The GK-play has developed, it has become more individual and flexible. - Scandinavian teams will bring an additional player whenever shorthanded and sometimes in specific situations as well. - Coaching has become more task oriented and less emotional with many nations. - Many teams play with righthanded players on the position RB in the first string, even if they have a lefty available. It seems that the switch has become a tactical element. 2. Specific findings - Some teams have wing players who are capable of playing either wing. - Most of the teams have one or two defence specialists, some switch the defence specialist with the PM in the offence. - Score runs of one team and then of the other one are still very common. 3. Weak points - Although the international attention was great, many matches suffered from a lack of spectators. - The performance of the referees was below expectation, analysis and solution of this problem are in progress. - The preliminary groups were imbalanced, B and D turned out to be stronger and closer than the other ones. - In case of an injury it seemed unlikely for the teams to compensate the elimination of a player of the first string. The new format with more rest days seemed to be an advantage for the level of the tournament overall. Of course this was a special situation due to the fact that there were two venues only available for the matches but in the future this fact has to be taken into consideration. In total it was a great event with a high number of good quality matches and with some surprising results as well as promising teams and players for the future. Women handball obviously is on a very good way, so let us look forward to even more attractive development in the future.